1995
DOI: 10.1097/00003086-199505000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction Using the Saddle Prosthesis Following Excision of Primary and Metastatic Periacetabular Tumors

Abstract: From 1988 to 1991, 17 patients with malignant periacetabular tumors underwent limbsparing surgery and reconstruction using the saddle prosthesis. There were 8 patients with primary malignant lesions (Group l), and 9 patients with metastatic or systemic tumor involving the periacetabular pelvis (Group 2). All resections included excision of the acetabulum. Patients ranged in age from 24 to 76 years (average, 59.8 years). Local control was achieved in all patients. Wide margins were obtained in all patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 0 publications
8
115
0
3
Order By: Relevance
“…The 20% infection rate in our series of patients is lower than reported rates in some series [3,4,18,26,27,36,39,41,45,46] and greater or comparable to the experience reported in other studies [1,8,12,13,19,20,29,30,38] ( Table 3). The overall infection rate in many series varied from 10% to 47% after internal hemipelvectomy [1, 3, 4, 8, 10, 12, 13, 18-20, 23, 25-27, 29, 30, 34, 36, 38-41, 45, 46], whereas it ranged from 11% to 38% in patients who had resection and endoprosthetic reconstruction [1,3,12,19,20,26,27,36,45,46]. Abudu et al [3] reported a 26% infection rate in a series of 35 patients undergoing endoprosthetic reconstruction with saddle prostheses.…”
Section: Discussionsupporting
confidence: 79%
“…The 20% infection rate in our series of patients is lower than reported rates in some series [3,4,18,26,27,36,39,41,45,46] and greater or comparable to the experience reported in other studies [1,8,12,13,19,20,29,30,38] ( Table 3). The overall infection rate in many series varied from 10% to 47% after internal hemipelvectomy [1, 3, 4, 8, 10, 12, 13, 18-20, 23, 25-27, 29, 30, 34, 36, 38-41, 45, 46], whereas it ranged from 11% to 38% in patients who had resection and endoprosthetic reconstruction [1,3,12,19,20,26,27,36,45,46]. Abudu et al [3] reported a 26% infection rate in a series of 35 patients undergoing endoprosthetic reconstruction with saddle prostheses.…”
Section: Discussionsupporting
confidence: 79%
“…As reported in the literature, the overall infection rate in several series varied from 12% to 47% after internal hemipelvectomy [1][2][3]10]. We had one major complication in the group undergoing intralesional excision whereas six of the 14 patients who underwent wide resection had major complications.…”
Section: Discussionmentioning
confidence: 65%
“…Surgical options include the use of autogenous bone grafts, allografts, compound osteosynthesis and/or an endoprosthesis [9,10]. Especially in cases of a less extended bony destruction of the peri-acetabular region (Harrington class II), several authors have described the use of acetabular support rings in combination with THA or reconstruction using saddle prostheses following excision of primary and metastatic peri-acetabular tumours [11][12][13]. Although they have reported good results immediately after surgery or during early follow-up, reconstruction failures or degradation of the functional status have been observed in a considerable portion of the patients, especially following implantation of saddle prostheses.…”
Section: Discussionmentioning
confidence: 99%